Villa Hügel - Buddensieg, Tilmann (Siedler, 1984)
Tilmann Buddensieg (Hrsg.), Knut Borchardt, Axel Föhl, Dorothee Nehring, Fritz Neumeyer, Karl Wolfgang Schümann, Michael Stürmer, Eduard Trier:
Keywords: Krupp; Alfred; Krupp family; Decoration and ornament; Architectural; Essen / R.b. Architektur; Bautechnik; Villa; Krupp; Historismus